Organization of a sporting event based on the act of December 2nd, 2021 on support for the preparation of the 3rd European Games 2023 - Borek, Dominik; Tomanek, Mateusz (Journal of Education, Health and Sport, 2023)
The management of a major sporting event is a multi-faceted issue that involves organizational, legal, social, economic and ethical layers. The article deals with a special sports event - the European Games. It is a multidisciplinary event that has the status of the so-called Continental Games. The competition offers the opportunity to obtain Olympic qualification in certain sports. It is the second such important sports event after EURO 2012 organized on Polish territory (Jankowski 2023). The issue of organizing a large-scale sports event will be presented from the perspective of applying the provisions of the Law of December 2, 2021 on Supporting the Preparation of the Third European Games in 2023. It should be borne in mind that this is a dedicated legal act established by the Polish legislator for the organization of this event. In the pages of this article, I will try to make a preliminary assessment of this document and encourage a broader discussion of the European Games initiative itself. The latter in the international literature is only the backdrop of broader considerations and has not lived to see a serious academic discussion as to its attractiveness and real impact on a given local community and regional development. The research methods used in this study are the dogmatic-egg method, requiring the author to examine the poor views of doctrine to date and analyze the legal regulations on which I have relied in describing the management of a mass sports event such as the European Games. It should be emphasized that this is the third such event in a row, which so far has been mainly organized in urban space-Baku 2015, Minsk 2019. For the first time, the event involves the entire region and tourism promotion that touches not only the main organizing city-Krakow, but also a region like Malopolska. In addition, this is the first time an event of this stature has been organized in a city that is not the capital of a country.